Anarkisme Demonstrasi Mahasiswa: Studi Kasus Pada Universitas Islam Negeri Alauddin Makassar - HASSE J HASSE J (Jurnal Studi Pemerintahan, 2012)
This study aims to describe the phenomenon of violence in the student demonstrations in Makassar.Violence in the demonstrations, especially by students at several universities in Makassar is a sightfamiliar to the public. Submission of student aspirations through a demonstration is considered a veryeffective medium. However, the demonstration is always ended with a riot / violence. Metod collectionof data through observation of student development activities, demonstration activities, both insideand outside the college; in-depth interviews conducted on-campus students and stakeholders and thepublic; conducted group discussions with students who are involved or not in any demonstration;study documentation/literature do specifically to research and writing as well as opinion pieces innewspapers that are stored in several parties.Key words: Violence, Students, Demonstrations,